Implementation of Space Vector PWM for a Two-Phase Three-leg Voltage Source Inverter - Chakrapong Charumit; Vijit Kinnares (My University, 2008)
This paper proposes the implementation of a carrier-based balanced two-phase output space vector pulsewidth modulation (SVPWM) strategy for a three-leg voltage source inverter (VSI). The principle based on analogue and digital techniques is fully described. The space vector equivalent waveforms and SVPWM patterns are generated by a digital signal processor (DSP). The correctness of the proposed method is verified by calculated and experimental results.
Keywords: Space vector; SIGNAL (programming language); Modulation (music); Three-phase; Multilevel Inverters and Converters